2005
DOI: 10.1002/ejic.200400879
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation in SnO2–Fe2O3 Nanopowders and Effects in Mössbauer Spectroscopy

Abstract: SnO 2 -Fe 2 O 3 nanopowders prepared by the polymeric precursor method were studied by combined conventional and high-resolution techniques. The powders treated at 500°C were analyzed by EDS local probe associated with HRTEM to directly detect surface segregation of Fe ions onto SnO 2 nanoparticles over a broad range of concentrations. The segregation of these ions controls the system microstructure by changing the surface energies and acting as nucleation sites for the formation of a Fe oxide phase (magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 24 publications
2
23
1
6
Order By: Relevance
“…Undoped and Ni-doped SnO 2 nanoparticles have been synthesized using the polymer precursor method (Pechini's method [10]). Tin citrate (Sn 2 -(C 6 O 7 H 4 )·H 2 O), obtained from SnCl 2 ·2H 2 O and citric acid precursors, and Ni(NO 3 ) 2 6H 2 O were used to produce the nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…Undoped and Ni-doped SnO 2 nanoparticles have been synthesized using the polymer precursor method (Pechini's method [10]). Tin citrate (Sn 2 -(C 6 O 7 H 4 )·H 2 O), obtained from SnCl 2 ·2H 2 O and citric acid precursors, and Ni(NO 3 ) 2 6H 2 O were used to produce the nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…When higher amounts of Co 3 O 4 (5 mol%) [10] or CoO (2 mol%) [27] are added to SnO 2 in mixed oxide procedures, the diffraction peaks of Co 2 SnO 4 are visible without the need of magnification of the XRD patterns. On the other hand, it has been reported that there is a low probability for iron to extensively form a solid solution with tin oxide because of the different crystalline structure between SnO 2 and Fe 2 O 3 [28]. Nevertheless, the high density of sample SFN and results from previous works [9,13] prove that a certain degree of solid solution formation of Fe in SnO 2 indeed takes place.…”
Section: Microstructural Properties Of Sintered Samplesmentioning
confidence: 86%
“…A validade deste modelo nesta situação é reforçada através das análises de microscopia eletrônica disponíveis na literatura para pós produzidos pelo mesmo método de síntese e mesmas concentrações [31,32]. Observase das micrografias que as partículas são relativamente isotrópicas, reforçando a hipótese do uso da Equação (A) para o cálculo das energias.…”
Section: Energia De Superfície Do Sno 2 Dopadounclassified
“…Nota-se que a presença dos aditivos diminui a energia de superfície dos materiais dopados em relação ao SnO 2 puro. Isso é consistente com as observações da literatura relativas à segregação dos aditivos na superfície do SnO 2 [4,17,31,32]. Essa segregação leva à redução em σ conforme a Equação B.…”
Section: Energia De Superfície Do Sno 2 Dopadounclassified